A CFD model for analysis of performance, water and thermal distribution, and mechanical related failure in PEM fuel cells - Al-Baghdadi, Maher A.R. Sadiq (Research Centre for Electrical Power and Mechatronics, Indonesian Istitutes of Sciences, 2016)
This paper presents a comprehensive three–dimensional, multi–phase, non-isothermal model of a Proton Exchange Membrane (PEM) fuel cell that incorporates significant physical processes and key parameters affecting the fuel cell performance. The model construction involves equations derivation, boundary conditions setting, and solution algorithm flow chart. Equations in gas flow channels, gas diffusion layers (GDLs), catalyst layers (CLs), and membrane as well as equations governing cell potential and hygro-thermal stresses are described. The algorithm flow chart starts from input of the desired cell current density, initialization, iteration of the equations solution, and finalizations by calculating the cell potential. In order to analyze performance, water and thermal distribution, and mechanical related failure in the cell, the equations are solved using a computational fluid dynamic (CFD) code. Performance analysis includes a performance curve which plots the cell potential (Volt) against nominal current density (A/cm2) as well as losses. Velocity vectors of gas and liquid water, liquid water saturation, and water content profile are calculated. Thermal distribution is then calculated together with hygro-thermal stresses and deformation. The CFD model was executed under boundary conditions of 20°C room temperature, 35% relative humidity, and 1 MPA pressure on the lower surface. Parameters values of membrane electrode assembly (MEA) and other base conditions are selected. A cell with dimension of 1 mm x 1 mm x 50 mm is used as the object of analysis. The nominal current density of 1.4 A/cm2 is given as the input of the CFD calculation. The results show that the model represents well the performance curve obtained through experiment. Moreover, it can be concluded that the model can help in understanding complex process in the cell which is hard to be studied experimentally, and also provides computer aided tool for design and optimization of PEM fuel cells to realize higher power density and lower cost.